The potential role of preventive and therapeutic immunonutrition strategies for pediatric food allergy: A mini-review - Coppola, Serena; Carucci, Laura; De Michele, Roberta; Berni Canani, Roberto (Frontiers in Nutrition, 2022)
Food allergy (FA) is one of the most common chronic conditions in the pediatric age. The gut microbiome (GM)-immune system axis is a critical factor affecting FA susceptibility. The dynamic and bidirectional crosstalk between GM and immune system starts from early life, and has a pivotal role in the first 1,000 days of life. Nutritional factors during this crucial period mainly influence the proper GM-immune system function across the lifespan. Immunonutrition strategies, applied from the conception, could represent an innovative target for the prevention and treatment of pediatric FA. In this Mini-Review we described the potential preventive and therapeutic role of Immunonutrition strategies for pediatric FA, highlighting putative future perspectives in this field.